Unexpected cause of dyspnea: A case of pleomorphic adenoma in the trachea - Kaoutar Maslouhi; Eric Michel Charlemagne Kessi, Junior; Safae Lanjeri; Kaouthar Sfar; Salma Malak Ridah; Youssef Omor; Rachida Latib; Sanae Amalik (Radiology Case Reports)
Pleomorphic adenoma (PA) is the most common benign histological form of salivary gland tumors, particularly in the parotid gland, primarily affecting women between the ages of 40 and 60. However, its occurrence in the trachea is very rare. This article reports the case of a 48-year-old woman presenting with progressive dyspnea and weight loss, initially suspected of having a pulmonary embolism. A chest CT scan revealed a nearly circumferential tracheal lesion with 2 nodules partially obstructing the tracheal lumen. Histological analysis confirmed the presence of a pleomorphic adenoma of the “salivary gland” type. Although rare, tracheal pleomorphic adenoma should be considered in the differential diagnosis of tracheal tumors. MRI is the preferred examination for detecting tumors in the parotid gland region, offering excellent tissue differentiation. Surgery remains the treatment of choice to prevent recurrence.